Comparison of the MOSFET Response at Exposed of the X-Ray and Gamma Radiation - S. A. Mokrushina; N. M. Romanov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Electromagnetic or ionizing radiation (IO) has great influence for radiation resistance of MOSFETs (metal–oxide–semiconductor field-effect transistors) and integrated circuits. Oxide, for the studied samples, is silicon dioxide, which acts as a dielectric in MOS structure. Currently, in literature there is no unambiguous idea of complete radiation response of MOSFETs to various types of ionizing radiation.Aim. To study radiation response of MOSFETs under influence of gamma and X-ray irradiation; to study effect of applied external potential of a gate substrate.Materials and methods. A total dose effect of gamma and X-ray radiation on the threshold voltage of MOSFET with a polysilicon gate and a gate oxide thickness of 120 nm with an applied external potential (-3, -2, 0, 3, 5, 10) V was studied. For gamma irradiation radionuclides cesium-137 with an energy of gamma quanta of 662 keV were used. X-ray tube with tungsten-rhenium cathode operated in modes 40 keV and 90 mkA was used as a source of X-ray radiation. Dose and time dependences of the change in the threshold voltage of n- and pchannel MOSFET were analyzed. It was performed that the influence of gamma and X-ray radiation led to the same effects in the studied structures. The maximum radiation response of MOSFETs was observed at high positive gate-substrate potentials. The approximation parameters associated with the concentration and capture cross sections of traps responsible for the formation of charges in the dielectric gate through irradiation were determined.Results. Strong influence of gamma and X-ray radiation led to the same effects in the studied structures. The applied voltage to the MOS structure during X-ray irradiation had a strong effect on their radiation response. The maximum radiation response of MOSFET at high positive gate-substrate potentials was observed. Proportionality coefficients to ensure the coincidence of the initial sections of the dose dependences for various applied gate-substrate potentials during irradiation were introduced. The coefficients allowed one to compare active and passive modes of operation of the X-ray emitter. Correction factors depended on the polarity of the applied gate-substrate potential. For negative potential, the proportionality coefficient value was 38.5. For the case of positive polarity the coefficient did not depend on the applied potential and the value was 120.Conclusion. The study allows one to determine the coefficients for dose dependences of threshold voltage changes. For the first time, to establish a numerical relations between the effects of various types of radiation sources at irradiation doses up to 1.9 · 104 Rad and proportionality coefficients becomes possible. It allows one to take into account the influence of applied potentials during irradiation on the radiation response of MOS structures.